2019
DOI: 10.1085/jgp.201912360
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the molecular target sites for CFTR potentiators GLPG1837 and VX-770

Abstract: Identification of the binding sites for small molecules that alleviate gating defects in CFTR would assist rational drug design for the treatment of cystic fibrosis. Yeh et al. identify two potential binding sites for prototypical CFTR potentiators at the interface of CFTR’s two transmembrane domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 75 publications
(134 reference statements)
5
65
0
Order By: Relevance
“…Interestingly, the simultaneous administration of ABBV-974 or ABBV-2451 with ivacaftor did not further enhance CFTR function, indicating that these molecules may act by the same mechanism of action (Yeh et al, 2017;Van der Plas et al, 2018). In fact, recent reports demonstrated that ABBV-974 and ivacaftor share a common binding site at the interface between the two TMDs near the kink of helix 8 (Liu F. et al, 2019;Yeh et al, 2019) (Figure 7). In a phase IIa trial, patients were subjected to a one-week ivacaftor washout before receiving three consecutive and increasing doses of ABBV-974.…”
Section: Potentiators: Restoring the Channel Gating And Conductancementioning
confidence: 93%
See 1 more Smart Citation
“…Interestingly, the simultaneous administration of ABBV-974 or ABBV-2451 with ivacaftor did not further enhance CFTR function, indicating that these molecules may act by the same mechanism of action (Yeh et al, 2017;Van der Plas et al, 2018). In fact, recent reports demonstrated that ABBV-974 and ivacaftor share a common binding site at the interface between the two TMDs near the kink of helix 8 (Liu F. et al, 2019;Yeh et al, 2019) (Figure 7). In a phase IIa trial, patients were subjected to a one-week ivacaftor washout before receiving three consecutive and increasing doses of ABBV-974.…”
Section: Potentiators: Restoring the Channel Gating And Conductancementioning
confidence: 93%
“…Some initial reports indicated that ivacaftor might bind to a region of amino acids at the NBD1/2 interface and the coupling helix of intracellular loop 1 (Veit et al, 2014) and/or the 'ball-and-socket' joint close to intracellular loop 4 (Byrnes et al, 2018). More recent studies provided direct evidence of the binding site of ivacaftor at the interface between TMDs by using electron cryomicroscopy and electrophysiological assays (Liu F. et al, 2019;Yeh et al, 2019). As chemical interactions are dynamic and the protein undergoes multiple conformational changes during channel opening and closure, some binding sites might also differ depending on the protein conformational state.…”
Section: Potentiators: Restoring the Channel Gating And Conductancementioning
confidence: 99%
“…1B, left). However, the application of 20 µM GLPG1837, a CFTR potentiator, which shares the same mechanism of action and binding sites as the FDA-approved drug Ivacaftor (Yeh et al 2017(Yeh et al , 2019a, greatly increased the current by 29.3 ± 3.4-fold (N = 5), indicating that the P o of the channel recorded was extremely low; as the maximal P o of an ion channel is 1, the P o of W1282X-CFTR must be <0.034 or 1/29.3, vs. ß0.4 for WT-CFTR (Yeh et al 2015).…”
Section: Chloride Currents Carried By a Mixture Of C-terminus Truncatmentioning
confidence: 99%
“…We next investigated the kinetic properties and the responses to pharmacological reagents of E60X-and G542X-CFTR. Specifically, we tested the effects of the high-affinity ATP analogue N(6)-(2-phenylethyl)-2deoxy-ATP (P-dATP), which works on the NBDs (Miki et al 2010), and the CFTR potentiator GLPG1837, which acts on CFTR's TMDs (Yeh et al 2017(Yeh et al , 2019a, on the kinetic parameters of endogenous read-through (preincubated with 3 µM VX-809) or drug-facilitated read-through (preincubated with 150 µM G418) proteins of E60X-and G542X-CFTR. Figure 9 shows representative single-channel recordings of E60X-CFTR from cells preincubated with VX-809 (black trace) or G418 (blue trace) with their respective responses to P-dATP and GPLG1837.…”
Section: Figure 7 Whole-cell Recordings Of E60x-and G542x-cftr Reveamentioning
confidence: 99%
“…Among the computational models listed above, only a few have been used to better characterize the binding mode of known F508del-CFTR-rescuing drugs, to virtually screen libraries of molecules aimed at the identification of new putative F508del-CFTR-binding compounds or to design new CFTR-targeted drugs [48,49]. On the contrary, a huge amount of computational studies has been developed in the attempt of clarifying at a molecular level the mechanism of action of F508del-CFTR-ligands, using several NBDs RX data [23,[50][51][52] or the more recent cryo EM structures [53].…”
Section: Cftr Computational Modelsmentioning
confidence: 99%